Trichoderma asperellum reduces phoxim residue in roots by promoting plant detoxification potential in Solanum lycopersicum L. (April 2020) - Chen, Shuangchen; Yan, Yaru; Wang, Yaqi; Wu, Meijuan; Mao, Qi; Chen, Yifei; Ren, Jingjing; Liu, Airong; Lin, Xiaomin; Ahammed, Golam Jalal
Abstract: Phoxim, a broad-spectrum organophosphate pesticide, is widely used in agriculture to control insect pests in vegetable crops as well as in farm mammals. However, the indiscriminate use of phoxim has increased its release into the environment, leading to the contamination of plant-based foods such as vegetables. In this study, we investigated the effect of Trichoderma asperellum (TM, an opportunistic fungus) on phoxim residue in tomato roots and explored the mechanisms of phoxim metabolism through analysis of detoxification enzymes and gene expression. Degradation kinetics of phoxim showed that TM inoculation rapidly and significantly reduced phoxim residues in tomato roots. Phoxim concentrations at 5d, 10d and 15d post treatment were 75.12, 65.71 and 77.45% lower in TM + phoxim than only phoxim treatment, respectively. The TM inoculation significantly increased the glutathione (GSH) content, the activity of glutathione S -transferase (GST) and the transcript levels of GSH, GST1, GST2 and GST3 in phoxim-treated roots. In addition, the activity of peroxidase and polyphenol peroxidase involved in the xenobiotic conversion also increased in TM + phoxim treatment. The expression of detoxification genes, such as CYP724B2, GR, ABC2 and GPX increased by 3.82, 3.08, 7.89 and 2.46 fold, respectively in TM + phoxim compared with only phoxim. Similarly, the content of ascorbate (AsA) and the ratio of AsA to dehydroascorbate increased by 45.16% and 57.34%, respectively in TM + phoxim-treated roots. Our results suggest that TM stimulates plant detoxification potential in all three phases (conversion, conjugation and sequestration) of xenobiotc metabolism, leading to a reduced phoxim residue in tomato roots. Graphical abstract: Image 1 Highlights: Trichoderma (TM) rapidly and significantly reduced phoxim residues in tomato roots. Secondary metabolism-related enzymes activity was induced by TM. TM inoculation enhanced glutathione content and GST activity. TM upregulated the expression of detoxification genes ( GSH1, GSTs, GR, ABC2, GPX ). TM promoted the phoxim metabolism by improving plant detoxification potential.